Food insecurity in ACP-countries: From Policy and Programme Interventions to Vulnerable Groups - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The overall conclusion of this summary report is the need for both adequate interventions, appropriate information and effective institutions in order to address the issue of food insecurity in ACP countries.